Differences across sexes on head-twitch behavior and 5-HT2A receptor signaling in C57BL/6J mice. (25th September 2022) - Jaster, Alaina M.; Younkin, Jason; Cuddy, Travis; de la Fuente Revenga, Mario; Poklis, Justin L.; Dozmorov, Mikhail G.; González-Maeso, Javier
Highlights: Head twitch response (HTR) provides a functional readout of psychedelic activity in rodent models. Differences across sexes in HTR has not been explicitly studied. The psychedelic DOI elicited more HTR in female as compared to male C57BL/6J mice. This sex-dependent effect was not observed in 129S6/SvEv mice. Pharmacokinetic properties of DOI differed among sexes in C57BL/6J mice. Abstract: Psychedelics, also known as classical hallucinogens, affect processes related to perception, cognition and sensory processing mostly via the serotonin 5-HT2A receptor (5-HT2A R). This class of psychoactive substances, which includes lysergic acid diethylamide (LSD), psilocybin, mescaline and the substituted amphetamine 1-(2, 5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI), is receiving renewed attention for their potential therapeutic properties as it relates to psychiatric conditions such as depression and substance use disorders. Current studies focused on the potentially clinical effects of psychedelics on human subjects tend to exclude sex as a biological variable. Much of the understanding of psychedelic pharmacology is derived from rodent models, but most of this preclinical research has only focused on male mice. Here we tested the effects of DOI on head-twitch behavior (HTR) – a mouse behavioral proxy of human psychedelic potential – in male and female mice. DOI elicited more HTR in female as compared to male C57BL/6J mice, a sex-specific exacerbated behavior that was not observed in 129S6/SvEv animals. Volinanserin (or M100907) – a 5-HT2A R antagonist – fully prevented DOI-induced HTR in male and female C57BL/6J mice. Accumulation of inositol monophosphate (IP1 ) in the frontal cortex upon DOI administration showed no sex-related effect in C57BL/6J mice. However, the pharmacokinetic properties of DOI differed among sexes – brain and plasma concentrations of DOI were lower 30 and 60 min after drug administration in female as compared to male C57BL/6J mice. Together, these results suggest strain-dependent and sex-related differences in the behavioral and pharmacokinetic profiles of the 5-HT2A R agonist DOI in C57BL/6J mice, and support the importance of studying sex as a biological variable in preclinical psychedelic research.